(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
A 13 Years old girl with bilateral buccally impacted maxillary canine, shows spacing in upper arch and esthetically unpleasant. Permanent canines are considered the foundation of esthetic smile and functional occlusion.1 Management of impacted maxillary canine is important because of its contribution to the esthetics and its role in establishing arch form. So, treatment protocol with management of the impacted maxillary canine cases is vital for the orthodontist and general dental surgeons. DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.16001 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 28-29